2007
DOI: 10.1177/1049732307306922
|View full text |Cite
|
Sign up to set email alerts
|

Inner Strength as Disclosed in Narratives of the Oldest Old

Abstract: The aim of this study was to illuminate the meaning of inner strength when very old as narrated by women and men 85 and 90 years old. The authors used a phenomenological hermeneutical method to analyze interviews from 11 women and 7 men, aged either 85 or 90, who scored high on scales measuring phenomena related to inner strength. The following themes emerged from the analysis: feeling competent in oneself yet having faith in others, looking on the bright side of life without hiding from the dark, feeling ease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 25 publications
7
82
0
1
Order By: Relevance
“…Development of the scale was inspired by empirical research on various aspects of inner strength among old people (e.g. Aléx et al, 2006;Nygren et al, 2007;Santamäki Fischer et al, 2008) and on a meta-theoretical analysis that resulted in the identification of four dimensions of inner strength: firmness, creativity, connectedness, and flexibility, with an understanding that inner strength relies on the interaction of these dimensions (Lundman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of the scale was inspired by empirical research on various aspects of inner strength among old people (e.g. Aléx et al, 2006;Nygren et al, 2007;Santamäki Fischer et al, 2008) and on a meta-theoretical analysis that resulted in the identification of four dimensions of inner strength: firmness, creativity, connectedness, and flexibility, with an understanding that inner strength relies on the interaction of these dimensions (Lundman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The total score ranges from 25 to 175, and the higher the score, the higher the degree of resilience. The scale was translated into Swedish and psychometrically tested by Nygren et al (2004) and Lundman et al (2007).…”
Section: Instruments For Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from this review reveal the multidimensional nature of older peoples' experiences of living with cancer, throwing into sharp relief both the sources of suffering endured and the resourcefulness and resilience (Nygren, Norberg, & Lundman, 2007) older people bring to managing a changed life.…”
Section: Experiencing Cancer In Oldmentioning
confidence: 99%
“…Acceptance may represent emotional equanimity that comes with the letting go of a struggle to regain what is lost or being taken away (Prigerson & Maciejewski, 2008). One study using a phenomenological hermeneutical method to analyse interviews from persons 85 to 90 years old found that an important subtheme was 'feeling an inner peace (that) comes from an acceptance of oneself as one is, and one's life as it has been and as it is' (Nygren, Norberg, & Lundman, 2007.The third possibility is that mindfulness allows for 'a deep, penetrative non-conceptual seeing into the nature of mind and world ' (Kabat-Zinn, 2003, p146), to learn and to recognize the impermanent nature of all phenomena experientially and phenomenologically, which is a fundamental insight of Buddhism (Nanamoli & Bodhi, 1995). Through mindfully attending to negative phenomena, such as self-critical thinking (such as 'my life is worthless'), one learns that such emotions and thoughts need not be feared or avoided and that they eventually pass away (Segal et al, 2002).…”
mentioning
confidence: 99%